Book design - A collection of short stories by Edgar Allan Poe - Drouin, Ashley (My University, 2022)
The goal of this project was to redesign a book or a collection of stories. This book consists of six short stories written by Edgar Allan Poe. Poe is known for his horror stories and poems that deal with mystery, death, and other macabre subject matter. The cover design includes a dripping blood illustration above a rich red background. The colour and design of the cover represent murder and death, which are major themes present in Poe’s writing. The typeface is a clean sans-serif font written in large white letters which gives the book a modern feel and contrasts against the red. The inside cover is black with white illustrations of a cat and a heart. These two illustrations are images that relate to two of Poe’s most well-known stories, The Tell-Tale Heart and The Black Cat. The interior includes a small illustration at the beginning of each story and a black and white texture on the left page. Each illustration and texture is different and represents a specific symbol, theme, or emotion of that particular story. Lapture Display is used for the chapter openings, a serif typeface with jagged and sharply cut edges. This typeface works well with Poe’s work due to its edginess and gives the book an unsettling feel. The illustrations play off of this font due to their use of simple black lines with a mixture of soft curves and sharp points.
Presented on April 21, 2022 at Student Research Day at MacEwan University in Edmonton, Alberta.
Keywords: typography; layout; book design; illustrations